Warehouse Management System to Improve Work Efficiency at an Apparel Company - Yunanto Herlaksono; Julbintor Kembaren; Friska Natalia (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
Efficiency and Productivity Improvement have been compulsory to all companies in garment industry, to be more competitive and become sustainable in the business. The focus of this study is in warehouse area where people are struggling with inaccurate data therefore creating inefficiency in working practices. Authors created questionnaires and interviews with users to understand on current working practices with required time to complete. The result of this study will be used to develop a software which is combined with RFID to help companies in managing all activities in warehouse. This study can also be used to give clear picture of problems/challenges that are being faced by factories, solution that can be implemented and potential benefits that can be gained from this solution. The companies will then need to prepare themselves for digital transformation, change the work methods from manual to digital, firmer SOP and be open-minded to new technologies.